Editorial for "Quantitative MRCP Imaging: Accuracy, Repeatability, Reproducibility, and Cohort‐Derived Normative Ranges. Issue 3 (2nd March 2020) - Krishna, Satheesh; McInnes, Matthew DF
Abstract : Level of Evidence: 5. Technical Efficacy: Stage 2 J. Magn. Reson. Imaging 2020;52:821–822.